Optimizing Data to Integrate Health and Social Care in Dublin 8- A SMART D8 PROJECT - Hayes, Catherine (SMART D8 and Trinity College Dublin, 2022)
Optimizing Data to Integrate Health and Social Care in Dublin 8 is a Smart D8- funded project that aims to maximise health and wellbeing in D8 by optimising use of healthcare data. It brings together local and national partners to together identify approaches to generating and jointly using data to support the delivery of integrated care responding to community needs for current and future patients.
PUBLISHED
Keywords: Digital Engagement; Inclusive Society; Health informatics